Engineering Stepped Structures on Hydroxyapatite Surfaces: A Potential Strategy to Modulate Bone Marrow Mesenchymal Stem Adhesion, Spreading, and Proliferation - Yongmei Wang; Fang Wang; Min Gong; Lidan Chen; Yun Wang; Pu Xu; Zhu Zeng; Zuquan Hu; Jin Chen (Journal of Functional Biomaterials)
Constructing the surface structures of hydroxyapatite (HA) materials is a promising strategy for orchestrating the cell behaviors of bone marrow mesenchymal stem cells (BMSCs), beneficial for advancing BMSC-based tissue repair and regenerative therapies. The majority of previous strategies have focused on fabricating artificial micro-/nano-scale geometric topographies or patterns on HA surfaces. Yet, constructing surface crystal defects has received insufficient attention and application, despite their importance as highlighted by theoretical calculations. This is largely due to the instability of crystal defects, which tend to be eliminated during crystallization. Here, given the fact that stepped structures are rich in stable crystal defects along their edges and kinks, we crafted HA dishes featuring stepped surfaces and utilized them to establish cell culture models of BMSCs. The outcomes revealed that the stepped structures markedly altered the physicochemical properties of HA surfaces and affected the cytoskeleton structures, spreading area, cell morphology, and focal adhesions of BMSCs in the cell culture model, resulting in inhibited cell adhesion. Given that YAP is a key mechanical sensitive factor, and its nuclear translocation is closely tied to cytoskeletal reorganization, the nuclear translocation efficiency of YAP has been investigated. The results showed that a changed cell adhesion could affect the nuclear translocation efficiency of YAP, which would be an important reason for the change in proliferation and differentiation ability of BMSCs. This work not only enhances the understanding of the responses of BMSCs to HA surface structures but also facilitates the design and optimization of HA materials. Moreover, our manufacturing method is facile and efficient, positioning it to potentially integrate with other processing techniques for the more effective and precise regulation of BMSCs.